Faktor-Faktor Yang Mempengaruhi Kondisi Kesehatan Keuangan Pemerintah Daerah Di Provinsi Sumatera Barat: Indonesia - Monica Monica (Politeknik Ganesha Medan, 2023)
The Health Conditions of Local Government Finances are useful for viewing and assessing the ability of local governments to manage their respective regional finances. Local governments are expected to maximize revenue and all the potential of the area they have. This is what triggers variations in the Financial Health Conditions in Regional Governments. This study aims to analyze the factors that influence variations in the Financial Health Conditions of Regency/City Regional Governments in West Sumatra Province in 2019-2021. This study uses 57 Financial Report data. This research is a quantitative study using multiple regression analysis to test the effect of each variable on the Financial Health Conditions of the Local Government. Data processing was carried out using SPSS version 26. The results showed that the factor influencing the Financial Health Conditions of Local Governments was Financial Efficiency. While population, community age profile, community welfare level, population density, local revenue, and cost of goods and services have no effect on the condition of the financial health of local governments. This shows that the Regency/City Regional Governments in West Sumatra Province have been able to manage Regional Government expenditures, especially personnel expenditures, so that the Regional Governments can carry out Financial Efficiency well.